Genetic characteristics of mitochondrial DNA was associated with colorectal carcinogenesis and its prognosis. - Jae-Ho Lee; Ilseon Hwang; Yu-Na Kang; In-Jang Choi; Dae-Kwang Kim (PLoS ONE, 2015)
Clinical value of mitochondrial DNA has been described in colorectal cancer (CRC). To clarify its role in colorectal carcinogenesis, mitochondrial microsatellite instability (mtMSI) and other markers were investigated in CRCs and their precancerous lesions, as a multitier genetic study. DNA was isolated from paired normal and tumoral tissues in 78 tubular adenomas (TAs), 34 serrated polyps (SPs), and 100 CRCs. mtMSI, nucleus microsatellite instability (nMSI), KRAS mutation, and BRAF mutation were investigated in these tumors and their statistical analysis was performed. mtMSI was found in 30% of CRCs and 21.4% of precancerous lesions. Mitochondrial copy number was higher in SPs than TAs and it was associated with mtMSI in low grade TAs. KRAS and BRAF mutations were mutually exclusive in TAs and SPs. CRCs with mtMSI showed shorter overall survival times than the patients without mtMSI. In CRCs without nMSI or BRAF mutation, mtMSI was a more accurate marker for predicting prognosis. The genetic change of mitochondrial DNA is an early and independent event in colorectal precancerous lesions and mtMSI and mitochondrial contents are associated with the tubular adenoma-carcinoma sequence, resulting in poor prognosis. This result suggested that the genetic change in mitochondrial DNA appears to be a possible prognosis marker in CRC.